(untitled) (Journal of Hama University, 2026)
The current research aimed to identify the requirements for applying network leadership necessary to achieve institutional excellence in Syrian universities from the perspective of faculty members. It also sought to determine the significance of differences in the sample members’ mean scores on the questionnaire and its axes according to the following variables: (administrative tasks, years of experience, job title), as well as the interaction among them, using the multivariate analysis of variance (MANOVA) method. The analytical descriptive method was used, and the sample consisted of 150 faculty members from Tishreen University for the academic year 2024–2025. A questionnaire comprising 18 items across three main axes was employed. The results indicated that the requirements for applying network leadership to achieve institutional excellence in Syrian universities, from the perspective of faculty members, were at a moderate level. The axis "Infrastructure Requirements" ranked first with a moderate level of agreement, while the axis "Supportive Organizational Culture Requirements" came last, also with a moderate level of agreement. There were statistically significant differences in the mean scores of the sample members on the questionnaire and all its axes (except the first axis) based on the variable of administrative tasks, in favor of those with administrative responsibilities, and based on the variable of years of experience, in favor of those with more than 20 years of experience. However, there were no statistically significant differences based on the variable of job title or the interaction among the variables.